Worldwide study of the Sporadic E (Es) layer development during a space weather event. (December 2022) - Resende, L.C.A.; Zhu, Y.; Denardini, C.M.; Moro, J.; Da Silva, L.A.; Arras, C.; Chagas, R.A.J.; Chen, S.S.; Marchezi, J.P.; Carmo, C.S.; Picanço, G.A.S.; Silva, R.P.; et al.
Abstract: This work analyzes the worldwide development of Sporadic E (Es) layers in different regions during a High-Speed Solar Wind Stream (HSS) event on March 18, 2018. We used Digisonde data from auroral, equatorial, and low-middle latitude stations as the primary source for the analysis. We also examined a set of data from selected geomagnetic quiet days to compare the Es layer behavior in such regions. The preliminary results agreed with the understanding that the wind shear mechanism is the principal agent causing the Es layer behavior around the globe, except for the auroral region. Magnetometer and Total Electron Content (TEC) data showed that an undershielding electric field could also influence the Es layer formation over equatorial regions. Further, we observed auroral-type Es layer (Esa ) occurrence in the South American Magnetic Anomaly (SAMA). The particle precipitation dynamics between the auroral site and SAMA region have different ways of acting in the Esa layer formation. Finally, our analysis provided a deep understanding of the Es layer behavior in different latitudes during a specific space weather event. Highlights: The Es layer development was analyzed in different regions over the globe. We observed that the atypical Es layer development due to the irregularities in low-middle and equatorial stations. The differences in the Esa layer formation between the auroral site and the SAMA region are reported .